CheckGPT - Neo, Celene (Nanyang Technological University, 2025)
Recent advancements have led to the widespread adoption of generative artificial intelligence (GAI) chatbots such as ChatGPT, Gemini, and Perplexity. Despite their articulate and coherent responses, several concerns about using GAI chatbots have been raised. In particular, the issues surrounding inaccuracies produced in their responses. Students — key users of GAI chatbots — are typically vulnerable to accepting inaccurate chatbot responses. However, both global and local initiatives have largely overlooked this issue.